Corporate Tax Aggressiveness and Insider Trading1. (2nd December 2018) - Chung, Sung Gon; Goh, Beng Wee; Lee, Jimmy; Shevlin, Terry
ABSTRACT: We examine the association between corporate tax aggressiveness and the profitability of insider trading under the assumption that insider trading profits reflect managerial opportunism. We document that insider purchase profitability, but not sales profitability, is significantly higher on average in more tax aggressive firms. We also find that the positive association between tax aggressiveness and insider purchase profitability is attenuated for firms with more effective monitoring and is accentuated for firms with a more opaque information environment. In addition, we provide empirical evidence that tax aggressiveness is significantly associated with greater insider sales volume in the fiscal year prior to a stock price crash. Finally, we find that the association between tax aggressiveness and insider purchase profitability weakens after the introduction of FIN 48, consistent with the increased transparency of tax positions under the new disclosure requirement reducing insiders' information advantage and hence their ability to profit from insider trading. To the extent that insider trading profits reflect managerial opportunism, our results are consistent with managers exploiting the opacity arising from tax aggressive activities to extract rent from shareholders, particularly those shareholders who sold their shares to the managers. Our findings are particularly important in light of the number of studies relying on the agency view of tax avoidance to develop arguments or to draw inferences.